Optimization of The Educational Environment Using Digital Tools and Technologies - Askarova, Cholpon; Aitbai kyzy, Aigul; Shevchenko, Volodymyr; Kuchmenko, Oleksandr; Scherbak, Lyudmyla (International Journal of Basic and Applied Sciences, 2025)
The purpose of the study is to evaluate the effectiveness of using digital tools and technologies in the educational process to optimise learning. The methodology includes an experiment with 200 students who were divided into control and experimental groups. The experiment consists of three stages: collecting data from participants for the experiment, using digital technologies by the experimental group, and re-evaluating learning success by comparing the academic results of both groups. The technologies are adapted by integrating with curricula, personalising content, using analytics to monitor progress, providing flexible learning formats, and implementing student feedback. The control group used traditional teaching methods, while the experimental group used modern digital tools. The experimental study found that the use of digital technologies in the learning process contributes to improving academic performance and student engagement. After one semester of study, the average score of students in the experimental group increased from 75.3 to 89.7, while in the control group it increased only from 74.5 to 84.1. Attendance in the digital group increased from 88 to 92 academic hours, and the number of active responses increased from 17 to 25. Participation in group projects increased by 20%, and the frequency of participation in tests increased by 25% compared to the control group. The analysis of the obtained data confirms that the integration of modern digital tools into the educational process not only increases the efficiency of mastering the material but also reduces the time spent on learning compared to the old methods.